2023
DOI: 10.1002/admi.202202469
|View full text |Cite
|
Sign up to set email alerts
|

Improved Silicon Surface Passivation by ALD Al2O3/SiO2 Multilayers with In‐Situ Plasma Treatments

Abstract: total fixed negative charge density Q tot of ≈1 × 10 13 cm −2 in combination with a low interface defect density D it of ≈1 × 10 11 eV −1 cm −2 . [4][5][6][7][8][9] While the low D it represents a rather good chemical surface passivation, the high negative Q tot causes a reduction of the electron density at the surface, which results in an important field effect contribution to the c-Si surface passivation. Thus, this high negative Q tot induces an inversion layer on n-type Si surfaces, while an accumulation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It can be observed that without passivation, (0 min curve) the forward and inverse currents are close in magnitude, resembling an ohmic contact. With an increase in passivation time, the inverse saturation current decreases several orders of magnitude and this is attributed to a reduction in the density of silicon dangling-bonds by the passivation procedure [21][22][23][24]. The resulting chemical oxide layer (IPL formed after passivation) has a much lower defect density than the original silicon surface, which reduces the number of carrier trap states and improves the quality of the silicon-oxide interface [21].…”
Section: Aluminum Schottky Diodesmentioning
confidence: 99%
“…It can be observed that without passivation, (0 min curve) the forward and inverse currents are close in magnitude, resembling an ohmic contact. With an increase in passivation time, the inverse saturation current decreases several orders of magnitude and this is attributed to a reduction in the density of silicon dangling-bonds by the passivation procedure [21][22][23][24]. The resulting chemical oxide layer (IPL formed after passivation) has a much lower defect density than the original silicon surface, which reduces the number of carrier trap states and improves the quality of the silicon-oxide interface [21].…”
Section: Aluminum Schottky Diodesmentioning
confidence: 99%